Influence of surface roughness of carbon materials on human osteoblast-like cell growth - Starý, Vladimír; Douděrová, Margita; Bačáková, Lucie (Journal of biomedical materials research. Part A, 2014)
This article presents a study of the dependence of the biocompatibility of a carbon-based material, namely a 2D C/C composite, on mechanical and chemical surface modifications. The mechanical modifications were surface grinding and polishing, and chemical modifications were made by depositing thin layers of pyrolytic carbon, titanium-carbon and DLC layers. Human osteoblast-like MG 63 cells were cultivated on these materials. The densities of the cells after one-day cultivation and after four-day cultivation, and the average cell spreading area after one-day cultivation, were evaluated in dependence on particular surface roughness parameters. The minima of the cell density on pyrolytic carbon and titanium-carbon layers were found; they were connected with the maxima of the average cell area. For DLC, the cell area decreased as the roughness parameter Ra increased in the range 0.1-10 µm, although the minimum appeared for the density of the cells. Using a multivariate test, the dependences of the biocompatibility parameters on the layer material and on surface grinding were statistically significant. The results suggest that the optimal roughness parameters for MG 63 cell on carbon based surface were Ra ∼ 3.5 µm, RSm ∼0.03-0.08 mm, Rsk ∼0 or negative and Rku ∼ 20, DLC being the best material choice. These values of roughness were obtained by simple mechanical grinding of substrate and coating by DLC layer.
Keywords: Cell Proliferation; povrchové vlastnosti; buněčné linie; Osteoblasts; Surface Properties; osteoblasty; titan; biokompatibilní materiály; Humans; Titanium; proliferace buněk; Carbon; Cell Line; Biocompatible Materials; uhlík; lidé